Genomic Characterization of Chicken Anemia Virus in Broilers in Shandong Province, China, 2020–2021 - Liu, Ling; Li, Yuyan; Yin, Mingrong; Zhao, Peng; Guo, Longzong; Wang, Yixin (Frontiers in Veterinary Science, 2022)
Chicken infectious anemia (CIA), caused by chicken anemia virus (CAV), is an immunosuppressive disease characterized by growth retardation, aplastic anemia, lymphoid depletion, and immunodepression in young chickens. In this study, 33 novel CAV strains were isolated from broilers in Shandong Province during 2014–2015. Phylogenetic analysis of full-length genome sequences showed that most novel CAV strains isolated in this study were scattered across different branches, but mainly clustered in two genotypes, indicating a certain regional characteristic. Analysis of VP1 protein identified several amino acid substitutions which were relevant with the virulence and virus spread efficiency. Interestingly, four putative DNA recombination events were detected in the genomes of novel isolated CAV strains. In summary, this study demonstrated a genomic diversity of CAV in broilers isolated in Shandong Province during 2020–2021, and provided information for the further study of CAV molecular epidemiology and viral evolution.